Laboratory and Field Tests of Hardness and Wear Resistance of Heat-Treated Steel Samples and Machine Parts - Q., Tilabov B.; A., Sherbutaev J. (International Journal on Integrated Education, 2023)
This article describes the method of testing the hardness and wear resistance of hardened and released steel samples and machine parts in laboratory and field conditions. Samples with wear-resistant carbide coating obtained by casting according to expanded polystyrene gasified models are presented. The compositions, properties and abrasive wear resistance of cast steel samples before and after heat treatment with double phase recrystallization were studied. It is shown that heat treatment with double phase recrystallization increases the hardness and wear resistance of cast samples and parts by 2-3 times higher than serial ones.